(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
Image compression is the process of reducing the size of an image file while retaining its quality. When we compress a digital photograph or graphic file, it maintains the same image resolution but shrinks the amount of processing data that a computer uses to view or display that image which ultimately reduces the memory used for the storage of image files. There are various algorithms used for image compression. Linear Algebra(SVD) plays an important role in image compression. In this paper, we will discuss what is Singular Value Decomposition (SVD), how to compute singular value decomposition( SVD) andthe size of stored images is reduced by removing small singular values.We will use MATLAB to get the final output.